Estudo e ensaio de acoplamento de gerador fotovoltaico com inversor comercial para o acionamento de motor de indução trifásico em sistema de bombeamento de água - Carvalho, Edson Pessoa de (2019)
This work aims to study and test a conversion topology that fits the use in isolated photovoltaic generation systems driving induction motors on water pumping applications, with emphasis on low cost, easy maintenance and relative energy and operation efficiency. The characteristic of the design specifications to be experienced follows specials criteria such as safety, economy, small size, operability and satisfactory efficiency. The model to be experienced consists of a microprocessor controlled converter for maximum power transference of a PV generator to an industrial inverter, which triggers a commercial electric pump coupled to a three-phase induction motor, both of easy availability in the local market. Simulations and evaluations were performed using math and electrical circuit simulation softwares. The power circuits were evaluated and designed to be tested in the laboratory, with its results registered and demonstrated. To perform the experiment the following equipment and devices were used: PV array emulator E4360A - KEYSIGHT, push-pull type dc-dc isolated converter powered by current, a Texas Instruments´s (TIVA) 120 MHz processor, besides conditioned circuits of sensoring and driving. The microprocessor will perform control tasks for generator maximum power points by converter switchings. The inverter will perform load power control for nominal voltage parameter. Results and technical considerations will be presented.